Screening and Identification of Drought Tolerant Bread Wheat Landraces (Triticum aestivum L.) - Fatemeh Naderi; Fatemeh Bavandpori; Ezatolah Farshadfar; Mohsen Farshadfar (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī, 2020)
Drought is the abiotic stress to decrease yield potential. To screen and identify drought tolerant genotypes of bread wheat landraces, was studied in a randomized complete block design with three replications with two levels of stress (stress and non-stress environments) and 25 bread wheat genotypes, at the Razi University of Kermanshah in 2017-2018. Results of analysis of variance and mean comparison of morphological, physiological and biochemical traits showed that effect of genotype was significant for most of the traits under stress. Correlation coefficients showed a positive and significant result between yield with thousand seed weight and biological yield in both stress and non-stress conditions. Analysis of variance and mean comparisons showed that genotype No. 10 was superior under both stress and non-stress conditions. The results of correlation between drought stress indices showed that STI, MRP and biological yield were positively and significantly correlated with grain yield under both stress and non-stress conditions. Ranking of genotypes, based on sum of ranks, mean ranks and standard deviation of ranks, showed that genotypes 10, 15 and 18 were best rank and recognized as superior drought resistant genotypes, while genotypes 4, 16, and 22 were identified susceptible. Factor analysis in stress environment explained 80.55% of the variance by four main factors. Ward's cluster analysis under stress condition divided the genotypes into four groups. Grouping of genotypes were somewhat different due to different responses of bread wheat genotypes to water deficit stress and their differences in susceptibilies or relative resistancese.